Factores psicosociales que inciden en la adicción al tabaco en los estudiantes de Comunicación Social sección nocturna, Facultad de Ciencias Sociales de la Universidad Técnica de Machala, periodo lectivo 2013 – 2014. - Ortega Bustamante, Fernando Vicente (2014)
The means to reduce the damage caused by snuff and other psychotropic substances are an important part of political health . All psychoactive substances can be harmful to health , depending on how you take , in what quantities and how often the damage differs from one substance to another .